The impact of product quality on relationship quality: Empirical evidence from automotive industry - Hanaysha, Jalal R. M.; Abd Ghani, Noor Hasmini (Institut Pengurusan Kualiti (IPQ), UUM, 2016)
Building and maintaining successful relationship with customers has become the prime focus for many organizations.The ability of a brand to successfully manage customer relationships provides it with better opportunities for improving its competitive advantage. Past research paid less attention to examine the effect of product quality on relationship quality and its dimensions; brand trust, brand commitment, and brand satisfaction.Therefore, this paper intends to fill this gap and examine the effect of product quality on creating relationship quality in Malaysian automotive market. Several shopping centres in Northern region of Malaysia were utilized to conduct this study, whereby a survey using systematic sampling technique was administered to 384 passenger car users.The empirical results, using structural equation modeling (SEM), supported all the hypotheses. Particularly, the results revealed that product quality has significant positive effect on brand trust, brand commitment, and brand satisfaction. The results also indicated that product quality plays an important role in affecting overall relationship quality.The study is limited to individual customers in Northern region of Malaysia.Future studies may apply this work to organizational level, and expand it to other industry and country contexts in order to grasp better insights on role of product quality in influencing customer brand relationship.